Effect of growth regulators on floral malformation in mango (Mangifera indica L.) cv. Amrapali (Indian Journal of Arid Horticulture, 2025)
Mango is a unique species in fruit trees with respect to growth, specific nature and diversity. Like other crops, it is prone to various biotic and abiotic stresses being major obstacle to mango production. Amongst biotic and abiotic problems of mango, Floral malformation has become a crux with yield losses ranging from 60% to 80. A field experiment was conducted to assess the effect of auxin and ethrel on floral malformation in mango. Studies were undertaken on 18 years old mango trees of Amrapali. The selected trees were sprayed "on year" with different concentration of auxin (NAA) viz. 150 ppm, 175 ppm & 200 ppm., etheral viz. 300 ppm, 400 ppm & 500 ppm and distilled water in the first week of October. The result revealed that PGR particularly NAA@ 200ppm had significantly effect on maximum (65.92) percentage of healthy inflorescences per shoot and (21.46) percentage of hermaphrodite flowers per inflorescence as compared to rest concentrations of PGRS. Similar this PGR spray showed highest 3.42 and 0.63 average number of fruits set and retention per panicles, respectively followed by ethrel @ 500 ppm. While the lowest hermaphrodite flowers, fruits set and retention per panicle was found in control (distilled water spray), but under this treatment maximum percentage (75.96) of male flowers per inflorescence was noted. From the above study, it can be concluded that exogenous spray of NAA @ 200 ppm applied before flower and fruit bud differentiation can reduce the malformed panicles to the extent of about seventeen percent. Perfect flowers (hermaphrodite) can also be increased both in normal as well as malformed panicles which helpful for higher fruits set and retention per panicle.
Keywords: Mango; Auxin; Ethrel; Panicles; Floral malformation; Inflorescence.